Inclusive Communication in Public Service Innovation "Si Nduk KEREN” as Media for Civic Engagement in Pacitan Regency - Winarsih, Atik Septi; Kencono, Dewi Sekar; Yecyec, Faye Lorraine M.; Kasiwi, Aulia Nur (Jurnal Audiens, 2026)
This study aims to examine the quality of population administration services for vulnerable groups, which remains a challenge in realizing inclusive governance. The elderly and individuals with special needs often face access barriers, including mobility, information access, and service access. Proactive, inclusive service innovation is crucial to ensuring the equal fulfillment of administrative rights. This study aims to measure the level of satisfaction of the elderly and individuals with special needs with the implementation of the "Si nDuk KEREN" innovation program in Pacitan Regency and to identify service elements with the highest and lowest scores as a basis for service improvement. The study used a simple mixed-methods approach, combining a quantitative component (measuring nine service elements in accordance with national regulations) and a qualitative component (in-depth field findings to explain the factors underlying the scores). The study distributed the Community Satisfaction Index to 50 respondents. The results show that the elements of requirements and service products received the highest satisfaction scores, indicating procedural clarity and certainty of service outcomes. In contrast, elements of service time, staff competence, and facilities and infrastructure received relatively lower scores, primarily due to resource limitations, geographical challenges, and the need to adjust services for the elderly and individuals with special needs. Despite logistical challenges in data collection and field service delivery, the program significantly increased access to population administration services through home visits and free collective services. These findings confirm that the "Si nDuk KEREN" innovation contributes to strengthening inclusive governance, and that improvements in time efficiency, staff capacity building, and the provision of more vulnerable-friendly facilities are needed.